Empowerment and embodiment for collaborative mixed reality systems. (2nd May 2018) - Pan, Ye; Sinclair, David; Mitchell, Kenny
Abstract: We present several mixed‐reality‐based remote collaboration settings by using consumer head‐mounted displays. We investigated how two people are able to work together in these settings. We found that the person in the AR system will be regarded as the "leader" (i.e., they provide a greater contribution to the collaboration), whereas no similar "leader" emerges in augmented reality (AR)‐to‐AR and AR‐to‐VRBody settings. We also found that these special patterns of leadership only emerged for 3D interactions and not for 2D interactions. Results about the participants' experience of leadership, collaboration, embodiment, presence, and copresence shed further light on these findings. Abstract : We present several mixed reality based remote collaboration settings by using consumer head‐mounted displays. We investigated how two people are able to work together and found differences in collaborating and performing the task in these settings, with evidence supporting the notion that immersion confers leadership advantage. The results draw lessons for collaborative mixed reality and for the study of leadership, collaboration, embodiment, presence, and co‐presence.